Phospholipase A and acyltransferase 4/retinoic acid receptor responder 3 at the intersection of tumor suppression and pathogen restriction - Zhao, Jian-Yong; Yuan, Xiang-Kun; Luo, Rui-Zhen; Wang, Li-Xin; Gu, Wei; Yamane, Daisuke; Feng, Hui (Frontiers in Immunology, 2023)
Phospholipase A and acyltransferase (PLAAT) 4 is a class II tumor suppressor with phospholipid metabolizing abilities. It was characterized in late 2000s, and has since been referred to as ‘tazarotene-induced gene 3’ (TIG3) or ‘retinoic acid receptor responder 3’ (RARRES3) as a key downstream effector of retinoic acid signaling. Two decades of research have revealed the complexity of its function and regulatory roles in suppressing tumorigenesis. However, more recent findings have also identified PLAAT4 as a key anti-microbial effector enzyme acting downstream of interferon regulatory factor 1 (IRF1) and interferons (IFNs), favoring protection from virus and parasite infections. Unveiling the molecular mechanisms underlying its action may thus open new therapeutic avenues for the treatment of both cancer and infectious diseases. Herein, we aim to summarize a brief history of PLAAT4 discovery, its transcriptional regulation, and the potential mechanisms in tumor prevention and anti-pathogen defense, and discuss potential future directions of PLAAT4 research toward the development of therapeutic approaches targeting this enzyme with pleiotropic functions.